Pemberian Senam Hipertensi Pada Lansia Terhadap Penurunan Tekanan Darah Lansia Dengan Hipertensi di Desa Namotongan Kecamatan Kutambaru Kabupaten Langkat - Tinah, Tinah; Triwibowo, Cecep; Siregar, Emi Inayah Sari; Sirait, Sri Hartati (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Hypertension is a significant health issue, particularly among the elderly, and can lead to severe complications if not managed properly. This community service program aimed to reduce blood pressure in elderly individuals with hypertension through regular hypertension exercises. The program was carried out in Namotongan Village, Kutambaru District, Langkat Regency, in 2024, with 30 elderly participants. The activities were conducted from August to November 2024. Hypertension exercises were performed three times a week for 30 minutes, using YouTube as a guide. The program's goal was to provide accessible and non-pharmacological interventions for managing hypertension, promoting the adoption of a healthy lifestyle through physical activity. Blood pressure measurements were taken before and after the exercise sessions to assess the changes. The results showed a significant reduction in systolic blood pressure from an average of 150 mmHg to 140 mmHg, and diastolic blood pressure from 95 mmHg to 88 mmHg. Additionally, 50% of participants achieved normal blood pressure after following the exercise program regularly. The majority of participants (83.33%) adhered to the program until completion, showing high commitment and enthusiasm for the initiative. This community service program demonstrates that hypertension exercises are an effective non-pharmacological intervention for reducing blood pressure in the elderly. It highlights the importance of regular physical activity in hypertension management, particularly in underserved areas. The program has shown positive results and can serve as a model for similar initiatives in other regions, contributing to the improvement of elderly health and the reduction of hypertension prevalence.